Pengaruh Brand Image dan Promosi Sosial Media terhadap Keputusan Pembelian melalui Kepuasan Konsumen sebagai Variabel Intervening Studi Kasus pada Balisijuk.id Payakumbuh - Ganda Anhar; Vivi Nila Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Brand Image and Social Media Promotion on Purchase Decisions, with Consumer Satisfaction as an intervening variable in Balisijuk.id in Payakumbuh. In the digital era, a strong Brand Image and effective promotion strategies through social media are important factors in attracting interest and increasing Consumer Satisfaction, which ultimately influences purchase decisions. This research method uses a quantitative approach with purposive sampling techniques. Data was collected through questionnaires distributed to Balisijuk.id consumers. Data analysis was carried out using multiple linear regression models and path analysis to test the direct and indirect relationships between variables. The results of the study show that Brand Image and Social Media Promotion have a significant effect on Consumer Satisfaction. Furthermore, Consumer Satisfaction proved to be an intervening variable that strengthened the relationship between Brand Image, Social Media Promotion, and Purchase Decision. In other words, the more positive the Brand Image and the more effective the Social Media Promotion, the higher the Consumer Satisfaction, which ultimately drives the Purchase Decision. This research provides practical implications for business actors, especially Balisijuk.id, in designing more effective marketing strategies through strengthening Brand Image and optimizing Social Media Promotion to increase consumer satisfaction and purchase decisions Balisijuk.id.